2004
DOI: 10.1158/0008-5472.can-03-3501
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Channels Promoting Calcium Spikes and Waves in HT1080 Tumor Cells

Abstract: ABSTRACT2؉ channel blockers nicardipine, SKF96365, diltiazem, and verapamil had no effect at appropriate doses. These results indicate that certain LVA and NVG channels regulate HT1080 cell motility. In addition to providing novel information regarding cancer cell motility, we suggest that it may be possible to design drugs that inhibit a key Ca 2؉ wave, thereby enhancing the efficacy of emerging therapeutic protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 53 publications
(50 reference statements)
4
64
0
1
Order By: Relevance
“…Many factors involved in cell migration are regulated by Ca 2+ including myosin light chain kinase, calpain, gelsolin, calcineurin, and integrins [1,11,12,23]. In fact, repetitive Ca 2+ transients or cytoplasmic Ca 2+ gradients were shown in migrating neurons, neutrophils, fibroblasts, eosinophils, tumor cells, and other cell types [5,16,18,22,26]. The precise temporal and spatial regulation of [Ca 2+ ] i is required for cellular motility.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors involved in cell migration are regulated by Ca 2+ including myosin light chain kinase, calpain, gelsolin, calcineurin, and integrins [1,11,12,23]. In fact, repetitive Ca 2+ transients or cytoplasmic Ca 2+ gradients were shown in migrating neurons, neutrophils, fibroblasts, eosinophils, tumor cells, and other cell types [5,16,18,22,26]. The precise temporal and spatial regulation of [Ca 2+ ] i is required for cellular motility.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, T-type channel blockers such as mibefradil and pimozide, which cannot distinguish between Ca v 3.1 and Ca v 3.2 channels, were used to investigate the regulation of cancer cell proliferation (13)(14)(15)(16)(17). Since there is a possibility that these isoforms exhibit different functions in tumors, if both isoforms are inhibited by such drugs to the same extent, the results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in prostate carcinoma cells, an increase in T-type Ca v 3.1 channel expression has been found to correlate with the inhibition of proliferation and the promotion of apoptosis (12). Alternatively, a number of reports have speculated on the progressive roles of T-type channels in tumor growth (13)(14)(15)(16). In addition to such conflicts, almost all these reports have not distinguished among T-type isoforms, since the currently available blockers that have been used have poor specificities for each isoform.…”
Section: Introductionmentioning
confidence: 99%
“…Ca v 3.2 channels are expressed in several cancer-derived cell lines, and blockage of the channel generates antiproliferative action (Roger et al, 2006, Panner & Wurster, 2006. T-type calcium channels have been found in lung carcinoma cells (OguroOkano et al, 1992) and calcium influx through different ion channels has been suggested to participate in migration and invasion of prostate, breast and fibrosarcoma cells (Monet et al, 2009;Yang et al, 2009;Huang et al, 2004).…”
Section: Calcium Channelsmentioning
confidence: 99%